Reconstruction of a pathologic mandibular fracture in a patient with pycnodysostosis using a free osteocutaneous fibula flap: A case report. Issue 6 (November 2015) - Sackeyfio, Robyn; Bernstein, Jaime L.; Kutler, David I.; Friedman, Joel M.; Spector, Jason A.
Abstract: Pycnodysostosis is an extremely rare autosomal recessive osteosclerotic disorder that stems from inactivation of the cathepsin K gene resulting in a predisposition to multiple fractures. We present the case of a 46-year-old male with a history of pycnodysostosis and over 30 previous fractures, who presented with a pathologic fracture of the right mandibular angle which was successfully reconstructed using a fibula osteocutaneous free flap.